1994
DOI: 10.1016/0928-8244(94)90102-3
|View full text |Cite
|
Sign up to set email alerts
|

Urban outbreak of a Brucella melitensis infection in an Argentine family: Clinical and diagnostic aspects

Abstract: An outbreak of Brucella melitensis in a family was studied. From the fourteen family members who ate unpasteurized goat cheese nine became ill. Patients included four females and five males of 8 to 75 years old. In seven of the patients the diagnosis was confirmed by positive blood culture for B. melitensis biovar 1. All the patients were analyzed by standard tube agglutination (STA) and standard tube agglutination with 2-mercaptoethanol (STA-2ME) tests at the time of diagnosis. In six of the patients, ELISA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…In dairy animals, microorganisms localize in the supramammary lymph nodes and these can continue to excrete them in milk (Cordes andCarter 1979, Refai 2003). People contract the disease by direct contact with contaminated fetal membranes or, more commonly, as a result of the consumption of contaminated unpasteurized milk and cheese products (Young 1983, Wallach et al 1994. Studies performed in different regions of Turkey have shown that B. melitensis is responsible for approximately 20% of the abortion cases in sheep (Arda et al 1987, Kenar et al 1990.…”
Section: Introductionmentioning
confidence: 99%
“…In dairy animals, microorganisms localize in the supramammary lymph nodes and these can continue to excrete them in milk (Cordes andCarter 1979, Refai 2003). People contract the disease by direct contact with contaminated fetal membranes or, more commonly, as a result of the consumption of contaminated unpasteurized milk and cheese products (Young 1983, Wallach et al 1994. Studies performed in different regions of Turkey have shown that B. melitensis is responsible for approximately 20% of the abortion cases in sheep (Arda et al 1987, Kenar et al 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Transmission to humans occurs by ingestion of infected raw milk and milk products or by exposure to infected animals. 3,4 Although brucellosis in animals has been the target of aggressive eradication programs in several countries, the morbidity associated with brucellosis in humans still remains considerably significant with severe economic consequences. Human brucellosis is a protean disease, but most bacteremic patients have the typical presentations of recurrent fever, lassitude, joint pain, and sweating at night.…”
Section: Introductionmentioning
confidence: 99%
“…None of the household members of the cases developed brucellosis during the 18 months of our follow-up. In previous studies, however, a high rate of family cases has been found in household members of brucellosis patients, 24,25,27,28 suggesting that the infection was not acquired at home in this outbreak. *Ami = Amikacin; Azi = Azithromycin; Doxy = Doxycycline; Gent = Gentamicin; Rif = Rifampin; Trime-Sulfa = Trimethoprim-Sulfamethoxazole.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Food-borne outbreaks have been reported in families or neighborhoods as a result of the ingestion of goat white cheese distributed to households. 6,[24][25][26][27][28] It is known that patients with Brucella infection may well be asymptomatic despite being proven by culture to be bacteremic. 29,30 Nonetheless, our present report reinforces the need for active surveillance and contact tracing after apparent point source outbreaks given the subclinical or early cases that are not identified in a timely manner because of non-specific symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation